AN EXPERIMENTAL STUDY OF THE SULFUR CONTENT IN BASALTIC MELTS SATURATED WITH IMMISCIBLE SULFIDE OR SULFATE LIQUIDS AT 1300°C AND 1.0 GPA - Jugo P.J.; Luth R.W.; Richards J.P. (My University, 2005)
The sulfur content in basaltic melts coexisting with either sulfide or sulfate melts was determined experimentally. The experimental conditions were in the range of 1300–1355°C and 1·0–1·6?GPa, conditions appropriate for the melting of the upper mantle above subduction zones. Under these conditions, both sulfide and sulfate were present as immiscible liquids, as inferred from the round geometries of the quenched sulfide and sulfate phases. The measured S content in basaltic melts saturated with sulfate liquids ([S] = 1·5 ± 0·2 wt %) was 10 times higher than the S content in basaltic melts saturated with sulfide liquids ([S] = 0·14 ± 0·02 wt %). In our experiments, sulfate liquids were stable at fO2 as low as ?FMQ = +1·85 [?FMQ = log (fO2)sample – log (fO2)FMQ, where FMQ is the fayalite–magnetite–quartz oxygen buffer], and evidence from other sources indicates that sulfates will be stable at lower fO2 in melts with lower activities of silica. Because chalcophile and highly siderophile elements, such as Cu, Ni, Au, and Pd, are partitioned preferentially into sulfide phases, melting of sufficiently oxidized sources, in which sulfides are not stable, would favor incorporation of these elements into the silicate melt produced. Such melts would have a higher potential to generate ore deposits. This study shows that the high sulfur contents of such oxidized basalts also means that relatively small amounts of such magmas can provide significant amounts of sulfur to exsolving volatile phases and account for the bulk of the sulfur expelled in some volcanic eruptions, such the 1991 eruption of Mount Pinatubo.